Letter (copy) : Spain - Citrine, Walter, 1887-1983
011-0096-001 WMC/WJB/AC/671 Mr James Loeb, Jr., 27th April 1937 North American Committee to Aid Spanish Democracy, 381, Fourth Avenue, New York, N.Y. Dear Sir, Spain We have your letter of 16th April, and sincerely thank you for the good work you have done in having printed for distribution in the United States the pamphlet "Catholics and the Civil War in Spain". With reference to the points you raise, we have got into touch with Señor Oliveira, and as soon as he is able to furnish us with the information you require, we shall be pleased to transmit it to you. Yours faithfully, Joint Secretary. 292/946/11/96